PEMBERIAN DUKUNGAN PSIKOSOSIAL PADA ANAK YANG MENGALAMI GANGGUAN DI ERA PANDEMI COVID-19 - Darmin Tuwu; Bahtiar Bahtiar; Ratna Supiyah; Ambo Upe (Universitas Halu Oleo, 2020)
This paper aims to elaborate on the psychosocial support provided by the supervisors and managers of the orphanage to 50 children living in the Social Institution for Children and Adolescents of the Social Service for Southeast Sulawesi Province. This qualitative descriptive study focuses on studying children who experience psychological disorders after undergoing long quarantine during the COVID-19 pandemic. Methods of data collection through observation, in-depth interviews, and Focus Group Discussion. The results of the study show that: First, 50 children have undergone self-quarantine for months in the home. Due to long-term quarantine, the children experience mental and social (psychosocial) disorders in the form of boredom, boredom, and stress. Second, the causes of psychosocial disorders in children are not only caused by the length of quarantine in the orphanage, the prohibition on going to school and the prohibition on visiting other important public places due to the implementation of social distancing and stay at home policies, as well as the difficulty of children understanding the subject matter. online while undergoing online learning at home. Finally, providing psychosocial support to children in difficult times like now is very necessary, considering that the closest people to the child (parents, supervisors, and institution managers) are people who know exactly about the problems and solutions faced by children for healing mental health, social, and child psychology.